Systemic Oxidative Stress, Aging and the Risk of Cardiovascular Events in the General Female Population - Bourgonje, Martin F.; Bourgonje, Arno R.; Abdulle, Amaal E.; Kieneker, Lyanne M.; la Bastide-van Gemert, Sacha; Gansevoort, Ron T.; Bakker, Stephan J. L.; Mulder, Douwe J.; Pasch, Andreas; Saleh, Jumana; Gordijn, Sanne J.; van Goor, Harry (Frontiers in Cardiovascular Medicine, 2021)
Introduction: Menopause is associated with increased cardiovascular risk, in which oxidative stress plays a pivotal role. Systemic oxidative stress is reflected by decreased levels of free thiols (R-SH, sulfhydryl groups), which are key components of the extracellular antioxidant machinery. In this study, we investigated the relation between serum free thiols as marker of oxidative stress and the female cardiovascular phenotype, as well as potential associations with the risk of cardiovascular (CV) events in pre- and postmenopausal women from the general population. Methods: Female participants (n=2,980) of the Prevention of REnal and Vascular ENd-stage Disease (PREVEND) cohort study were included. Serum free thiol concentrations were analyzed for associations with demographic, clinical, biochemical, and gynecological parameters, as well as with menopausal status and, prospectively, with the risk of CV events. Results: Postmenopausal women had significantly reduced levels of serum free thiols (4.8 ± 1.0 vs. 5.2 ± 1.0 μmol/g, P<0.001) compared to reproductive women. In multivariable analyses, serum free thiols were significantly associated with menopausal status (OR 0.70 [0.49-0.98], P=0.039), even when adjusted for potential confounding factors, except for age (P=0.550). Prospectively, serum free thiols were significantly associated with the risk of CV events (HR 0.52 [0.27-0.97], P=0.040), even with covariate adjustment, although this disappeared when correcting for age. Conclusion: In this study, we revealed serum free thiols to be strongly associated with the female cardiovascular phenotype as well as with female risk of CV events, where the influence of age itself seemed to outweigh that of female menopause. Future studies are warranted to further unravel the clinical utility of serum free thiol levels in the context of female cardiovascular risk management.